Design development of sustainable brick-waste geopolymer brick using full factorial design methodology. (17th March 2023) - Rihan Maaze, Mohammed; Shrivastava, Sandeep
Graphical abstract: Highlights: Valorisation of brick waste powder as precursor material was investigated through alkali activation. Design development of brick waste-based geopolymer brick was established by applying a fully factorial design an experimental design methodology. Physical mechanical properties of BWP-based bricks were investigated. 12M (NaOH solution), 2.5 (Alkaline solution ratio) and 50 °C (Curing temperature) were optimum parameters. Abstract: Rapid expansion in the worldwide infrastructure sector has led to a massive increase in construction and demolition waste (CDW), which was inadequately managed from a disposal and reuse point of view. In the present experimental study, brick waste powder (BWP) obtained from CDW was used as a precursor material. The current research focuses on the design development of BWP-based geopolymer brick mixes by applying full factorial design (FFD). Molarity (4M−12M), alkaline solution ratio (1.5–2.5), and curing temperature (40–60 °C) were the experimental factors that varied to find an optimum design mix. Sand-to-precursor and solid-to-liquid ratios were kept constant. Physical and mechanical properties of brick specimens were studied and reported in the paper. Multi-response optimizer, desirability analysis, and statistical analysis, i.e. Analysis of variance (ANOVA), were performed to identify the optimum mix. Based on the multi-response optimizer, the optimum mix was 12M2.5AS50°C. Furthermore, X-ray diffraction (XRD), scanning electron microscopy (SEM) – Energy dispersive X-ray spectra (EDX), Fourier transform infrared spectroscopy (FTIR), and Thermal gravimetric analysis (TGA) was performed to examine phase structure, morphology, and thermal resistance of the brick mixes. Statistical and microstructural analysis reveals that molarity, alkaline solution ratio and temperature curing were the significant governing factors in enhancing the properties.